The Acute Physiological Responses to Traditional vs. Practical Blood Flow Restriction Resistance Exercise in Untrained Men and Women - Freitas, Eduardo D. S.; Galletti, Bianca R. A.; Koziol, Karolina J.; Miller, Ryan M.; Heishman, Aaron D.; Black, Christopher D.; Bemben, Debra; Bemben, Michael G. (Frontiers in Physiology, 2020)
This study compared the acute physiological responses of traditional and practical blood flow restriction resistance exercise (tBFR and pBFR, respectively) and high- and low-load resistance exercise without BFR (HL and HL, respectively), as well as the potential sex differences within the aforementioned exercise methods. Fourteen men and fifteen women randomly completed the following experimental conditions: 1) tBFR, consisting of four sets of 30-15-15-15 repetitions of the bilateral horizontal leg press and knee extension exercises, at 30% of 1-RM, with a 13.5 cm wide pneumatic cuff placed at the most proximal portion of each thigh and inflated to a pressure equivalent to 50% of the participant’s total occlusion pressure; 2) pBFR, which was the same as the tBFR condition, except that an elastic band wrapped around the proximal portion of each thigh at a tightness of 7 on a 0 to 10 pressure pain perceived scale was used to reduce blood flow; 3) LL, same as the tBFR and pBFR protocols, but no BFR was applied; and 4 ) HL, consisting of 3 sets of 10 repetitions at 80% of 1-RM, with the same 1-min rest interval between sets and a 3-min rest period between exercises. At baseline, immediately post-, 5 min post-, and 15 min post-exercise, whole-blood lactate (WBL), indices of muscle swelling (muscle thickness and thigh circumference), hematocrit and plasma volume changes, were measured as well as superficial electromyography (sEMG) amplitude during exercise. There were no significant (p > 0.05) differences between the tBFR and pBFR exercise protocols for any of the physiological parameters assessed. However, significantly greater (p <0.05) WBL and sEMG values were observed for HL compared to the remaining exercise conditions. Finally, males displayed greater WBL levels than females at 15 min post-exercise. Interestingly, males also displayed significantly (p <0.05) greater sEMG amplitude than females within the low-load trials during leg press, but no significant (p <0.05) sex differences were observed during knee extension. In conclusion, tBFR and pBFR seemed to be capable of inducing the same acute physiological responses. Furthermore, males displayed greater responses than females for some of the physiological parameters measured.